REDUPLIKASI SEMANTIK BAHASA INDONESIA: TELAAH NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Lala Zulfian Adha Sulfa; Amirudin Rahim; La Yani (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
This research aims to depict the forms and meanings of semantic reduplication in the Indonesian language within the novel "Laskar Pelangi" written by Andrea Hirata. The methodology employed in this study is qualitative description. The research gathers written data from the text of the novel "Laskar Pelangi," authored by Andrea Hirata, which is collected through reading and note-taking techniques. Based on the research findings, three forms of semantic reduplication can be identified: the form involving free morphemes repeated with other free morphemes, totaling 40 instances; the form involving free morphemes repeated with bound morphemes, amounting to 32 instances; and the form involving bound morphemes repeated with other bound morphemes, present in five instances. Furthermore, semantic reduplication in the Indonesian language conveying meanings of various groups or collections of different types of words or basic forms is found in 24 instances. Semantic reduplication in the Indonesian language signifying intensive meanings is present in 36 instances of the gentle-soft type and 17 instances of the breakable-split type.